2005
DOI: 10.1007/s10549-005-9085-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of expression based markers for the detection of breast cancer cells

Abstract: While no one of the these markers efficiently detects all breast cancers, a combination of two or more could achieve a very high sensitivity in assaying for circulating or occult breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…Other authors have found no correlation between the presence of CK-positive cells in BM and Ki67 staining in primary breast tumours (Schindlbeck et al 2005). However, in a recent study that analysed SBEM protein expression in a large cohort (n = 300) of invasive breast cancers, negative association with Ki67 staining was found (Brown et al 2006). Interestingly, most circulating and micrometastatic tumour cells do not express the proliferation antigen Ki67 and may therefore remain in the state of dormant cell-cycle arrest (Pantel et al 1993;Muller et al 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other authors have found no correlation between the presence of CK-positive cells in BM and Ki67 staining in primary breast tumours (Schindlbeck et al 2005). However, in a recent study that analysed SBEM protein expression in a large cohort (n = 300) of invasive breast cancers, negative association with Ki67 staining was found (Brown et al 2006). Interestingly, most circulating and micrometastatic tumour cells do not express the proliferation antigen Ki67 and may therefore remain in the state of dormant cell-cycle arrest (Pantel et al 1993;Muller et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…In mammary tissues, including breast cancer, SBEM expression has been shown to be restricted to luminal epithelial cells (Allinen et al 2004). Although SBEM expression has been found in the ER-positive, well-differentiated, ''luminal epithelial-like'' breast cancer cell lines (Lacroix and Leclercq 2004), other studies have shown SBEM gene expression, as assessed by RT-PCR, in more than 90% of primary or metastatic breast cancers (Miksicek et al 2002;Colpitts et al 2002;Brown et al 2006). In a small subset of primary breast tumours Skliris et al (2008) have recently shown that SBEM mRNA was detected by RT-PCR in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Skliris et al [14] investigated SBEM expression by IHC in TAMs and its association with other established markers of prognosis and concluded that SBEM could identify a unique subset of breast cancers with poor prognosis. To date, most study on SBEM has been accumulated to gene and protein expressions in breast cancer by RT-PCR and IHC methods [14,22]. These techniques offer the reliability and potential of improved sensitivity for detection of micrometastatic tumor cells that are missed by conventional histopathological examination, whereas they are time-consuming and complicated for screening the outpatients in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer detection is currently based on physical examination and imaging (mammography, ultrasound, and MRI) [6], although emerging methods include direct examination of the cytomorphology of exfoliated cells [7], and the molecular analysis of tumor biomarkers in nipple aspirate fluid or in ductal lavage [8], [9], [10]. In the last decade, biomarker discoveries for breast cancer detection have focused on blood and/or tissue, using proteomic [11], [12], [13], [14], [15], [16], transcriptomic [17], [18], [19], [20], [21], and genomic approaches [22], [23]. In comparison to prognostic biomarkers [24], [25], [26], the development of detection biomarkers has been limited, mainly due to a lack of sensitivity and specificity for this clinical context [2], [27], [28].…”
Section: Introductionmentioning
confidence: 99%